Association of FMO3 Variants with Blood Pressure in the Atherosclerosis Risk in Communities Study. (18th February 2019) - Bryant, Tyler S.; Duggal, Priya; Yu, Bing; Morrison, Alanna C.; Shafi, Tariq; Ehret, Georg; Franceschini, Nora; Boerwinkle, Eric; Coresh, Josef; Tin, Adrienne
Abstract : Flavin containing monooxygenase 3 [ FMO3 ] encodes dimethylaniline monooxygenase [N-oxide-forming] 3, which breaks down nitrogen-containing compounds, and has been implicated in blood pressure regulation. Studies have reported conflicting results of the association of a common nonsynonymous variant, E158K (rs2266782), with hypertension. We examined the associations of E158K, along with rare and low frequency exonic variants (minor allele frequency [MAF]<5%) in FMO3 with hypertension, systolic blood pressure (SBP), and diastolic blood pressure (DBP). We included 7, 350 European Americans and 2, 814 African Americans in the Atherosclerosis Risk in Communities (ARIC) study with exome sequencing of FMO3 . The association of FMO3 variants with SBP and DBP was tested using single variant and gene-based tests followed by the replication or interrogation of significant variants in ancestry-specific cohorts based on Bonferroni corrected thresholds. E158K had significant association with higher SBP in African Americans in ARIC (p=0.03), and two low frequency variants had significant association with higher SBP in African Americans (rs200985584, MAF 0.1%, p=0.0003) and European Americans (rs75904274, MAF 1.7%, p=0.006). These associations were not significant with additional samples: E158K in a meta-analysis of SBP of African ancestry (N=30, 841, p=0.43) that included ARIC participants and the two low frequency variants in an independent ancestry-specific exome sequencing study of blood pressure (rs200985584, p=0.94; rs75904274, p=0.81). Our study does not support the association of E158K and low frequency variants in FMO3 with blood pressure and demonstrates the importance of replication in genetic studies.